Mathematics knowledge for teaching within a functional perspective of preservice teacher training (2008)
In this paper we look at some issues concerning the first two questions that frame Topic Study Group 27. On the one hand, we describe a functional perspective of preservice mathematics teacher training and learning. This perspective is based on the consideration of didactic notions as instruments to analyze the mathematical subject matter from different viewpoints. On the other hand, we propose some con-cepts and methods that can allow researchers explore preservice teachers learning and help trainers assess the impact of methods coursesÕ design and development.